2003
DOI: 10.1186/1741-7007-1-2
|View full text |Cite
|
Sign up to set email alerts
|

TbAGO1, an Argonaute protein required for RNA interference, is involved in mitosis and chromosome segregation in Trypanosoma brucei

Abstract: BackgroundRNA silencing processes are widespread in almost all eukaryotic organisms. They have various functions including genome protection, and the control of gene expression, development and heterochromatin formation. RNA interference (RNAi) is the post-transcriptional destruction of RNA, which is mediated by a ribonucleoprotein complex that contains, among several components, RNA helicases and Argonaute proteins. RNAi is functional in trypanosomes, protozoan parasites that separated very early from the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…Competency-One of the striking features of the T. brucei AGO1 N-terminal domain is the high representation of arginine-glycine-glycine (RGG) motifs, which make up almost 50% of the first 59 amino acids (16,36). In particular, between positions 9 and 59 there are 10 RGG motifs, which are part of an 11-amino acid repeating unit with the consensus sequence G(Y/R)RGGRGGG(E/F)G ( Fig.…”
Section: The Size Of the Tbago1 Rgg Domain And The Presence Of Arginimentioning
confidence: 99%
“…Competency-One of the striking features of the T. brucei AGO1 N-terminal domain is the high representation of arginine-glycine-glycine (RGG) motifs, which make up almost 50% of the first 59 amino acids (16,36). In particular, between positions 9 and 59 there are 10 RGG motifs, which are part of an 11-amino acid repeating unit with the consensus sequence G(Y/R)RGGRGGG(E/F)G ( Fig.…”
Section: The Size Of the Tbago1 Rgg Domain And The Presence Of Arginimentioning
confidence: 99%
“…Functional genomic studies in T. brucei have also shown that non-mitotic proteins could play a role in mitotic progression. For example, knockdown of TbAGO1, which itself is required for RNAi, produced abnormal mitotic phenotypes (10).…”
mentioning
confidence: 99%
“…However, in contrast to other organisms, only one RNAi component has so far been identified in the parasite. The polypeptide is a member of the AGO protein family and has been termed TbAGO1 (38,39). TbAGO1 is essential for RNAi in insect stage trypanosomes and was shown to be assembled in siRNA-associated ribonucleoprotein particles, which are important for the stabilization and/or generation of siRNAs (39).…”
mentioning
confidence: 99%